Developing Fisheries Clusters to Increase Competitiveness Through Production Integration, Scale Efficiency, and Strengthening Institutions in Sustainable Aquaculture Systems - Burhan Arianto; Naqilla Itsak Ramadhani; Anastasia Shafaa Nurayya; Violin Anathasya Athfal Two; Desti Diyan Mekar Meirika Diyana; Mukhamad Malik Al Najib; Risyad Aghniya Yahya; Jefri Anjaini; Asro Nurhabib (PT. Gyandharma Global Media, 2025)
The development of fisheries clusters is a strategic approach to improving the competitiveness of the aquaculture sector through production integration, scale efficiency, and institutional strengthening. Challenges faced by fisheries cluster development include environmental degradation, social inequality in the supply chain, global market instability, and weak governance. The purpose of this paper is to analyze the basic concept of fisheries clusters, the role of production integration, scale efficiency, and institutional strengthening in enhancing the competitiveness of the sustainable aquaculture sector. This paper demonstrates that optimally designed fisheries clusters can reduce operational costs, increase productivity, expand farmer access to technologies such as circulating water systems (RAS) and IoT, and strengthen the position of structured institutions.